Highly transparent and non-damaging modified polyurea composite coating, preparation method and application thereof
Patent Information
- Application Number
- CN202611067606.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-07-17
- Publication Date
- 2026-10-20
AI Technical Summary
在常规的免烧陶瓷应用涂料中,为解决这个问题,通常是加入硅油类的防涂鸦助剂,虽然能够达到易清洁性能,但是由于此类助剂是后期加入,干燥后助剂通常会上浮在涂层表面,从而导致折射的情况出现,导致艺术效果变化
本发明提供一种高透无损改性聚脲复合涂料及其制备方法与应用,所述高透性无损改性聚脲复合涂料包括A组分、B组分和有机溶剂,所述A组分利用聚碳酸酯二醇的-OH,与六亚甲基二异氰酸酯和异佛尔酮二异氰酸酯的-NCO部分反应生成带有氨酯键的脂肪族聚异氰酸酯预聚体,由于氨酯键的引入,能够提高复合涂料涂层的韧性以及对彩绘陶瓷的附着力。
Smart Images

Figure FT_1 
Figure FT_2 
Figure SMS_1
Abstract
Description
Technical Field
[0001] This invention belongs to the field of polymer composite coating technology, specifically, it relates to a high-transparency, non-destructive modified polyurea composite coating, its preparation method, and its application. Background Technology
[0002] Traditional painted ceramic artworks mostly use inorganic glazes, which are durable but limited in color. Moreover, this usually requires a second high-temperature firing, which is energy-intensive and costly. In recent years, richly colored organic pigments have been applied to the creation of painted ceramic artworks, achieving firing-free production. However, organic pigments mainly rely on physical adhesion to the ceramic substrate, resulting in poor weather resistance and susceptibility to environmental erosion and human-caused physical damage.
[0003] Currently, the industry commonly uses a method of coating the surface of painted ceramic artworks with a transparent polymer coating for protection, such as traditional acrylic resins and polyurethane varnishes. However, existing technologies have significant drawbacks. On the one hand, conventional coatings contain a large amount of highly polar and volatile organic solvents (more than 10%), such as benzenes and ketones, which can easily dissolve, soften, and swell the fragile organic pigments under the coating, causing brushstrokes to spread, colors to bleed, and even problems such as wrinkling, blistering, and peeling of the paint film. On the other hand, after the traditional protective coating has cured and cross-linked, the mismatch between the refractive index and the ceramic substrate results in poor leveling of the coating, creating a lens effect on the microscopic surface. This causes light refraction to produce "oblique shadows," distorting the visual effect of the artwork. In addition, conventional polymer materials are prone to yellowing under ultraviolet radiation, severely damaging the original light and color presentation of the artwork.
[0004] In addition to their use for simple collection, painted ceramic artworks may also be used in public places such as squares and parks. In such environments, the surface coating of painted ceramics needs to have certain easy-to-clean properties. In conventional coatings for non-fired ceramics, silicone oil-based anti-graffiti additives are usually added to solve this problem. Although this achieves easy-to-clean properties, because these additives are added later, they usually float on the surface of the coating after drying, causing refraction and altering the artistic effect.
[0005] Therefore, there is an urgent need in this field for a non-destructive polymer protective coating technology that can provide strong physical protection and easy cleaning performance without damaging the underlying organic pigments, and has high optical transparency and high fidelity. Summary of the Invention
[0006] The problem to be solved by the present invention is to provide a high-transparency, non-destructive modified polyurea composite coating, its preparation method and application. The composite coating can provide strong physical protection and easy cleaning performance for painted ceramics, without damaging the underlying organic pigments, and achieve high color fidelity while maintaining high optical transparency.
[0007] To solve the above problems, the present invention is achieved through the following technical solution: This invention provides a high-transparency, non-destructive modified polyurea composite coating, comprising component A, component B, and an organic solvent; Component A is an aliphatic polyisocyanate prepolymer, which is mainly obtained by polymerization reaction of hexamethylene diisocyanate, isophorone diisocyanate, polycarbonate diol, and organic bismuth. Component B is a composite resin, comprising the following raw materials in parts by weight: 100 parts of polysiloxane block-modified polyaspartic acid ester resin; 1 to 4 parts of nano-sized hydrophilic fumed silica; 0.5 to 5 parts of nano-zirconia; 0.5 to 3 parts of silane coupling agent; 1 to 2 parts of auxiliary agent; The polysiloxane block-modified polyaspartic acid ester resin is mainly obtained by Michael addition reaction of modified amino-terminated polysiloxane, alicyclic diamine, and dialkyl maleate. The amount of the organic solvent is 0.5 to 1 part, based on 100 parts by weight of the polysiloxane block-modified polyaspartic acid ester resin.
[0008] In some embodiments, the aliphatic polyisocyanate prepolymer is prepared by the following method: (1) Mix hexamethylene diisocyanate monomer and isophorone diisocyanate monomer in a molar ratio to obtain mixture A; (2) Polycarbonate diol is added to the mixture A to obtain mixture B; (3) Under constant temperature conditions of 70℃~90℃, an organic bismuth catalyst was added dropwise to the mixture B, and the reaction was carried out for 2h~4h to obtain mixture C; (4) Remove the unreacted free isocyanate monomers from the mixture C to obtain the aliphatic polyisocyanate prepolymer.
[0009] In some embodiments, the molar ratio of the hexamethylene diisocyanate monomer to the isophorone diisocyanate monomer is 1:1 to 3:1; The number-average molecular weight of the polycarbonate diol is 1000-2000; The amount of organic bismuth added is 0.02wt% to 0.05wt%.
[0010] In some embodiments, the molar ratio of -NCO to -OH in mixture B is 4:1 to 6:1; The mass fraction of -NCO in the mixture C is 10% to 15%.
[0011] In some embodiments, the polysiloxane block-modified polyaspartic acid ester resin is prepared by the following method: (1) The modified amino-terminated polysiloxane and alicyclic diamine were mixed in a molar ratio to obtain mixture D; (2) Under nitrogen protection, the mixture D is added dropwise to dialkyl maleate to obtain mixture E, wherein the molar ratio of -NH2 to -C=C- in mixture E is 1:1 to 1:1.05; (3) The mixture E is subjected to a Michael addition reaction at 40℃ to 60℃ for 12h to 24h to obtain mixture F; (4) The unreacted monomers in the mixture F are removed by vacuum to obtain the polysiloxane block-modified polyaspartic acid resin.
[0012] In some embodiments, the modified amino-terminated polysiloxane includes any one of amino-terminated diphenylsiloxane, polyether side-chain modified amino-terminated siloxane, amino-terminated poly(methylcyclohexyl)siloxane, and amino-terminated poly(methylcyclopentyl)siloxane. The alicyclic diamine includes any one of 4,4'-diaminodicyclohexylmethane and 3,3'-dimethyl-4,4'-diaminodicyclohexylmethane; The dialkyl maleate includes either diethyl maleate or dipropyl maleate. The number-average molecular weight of the modified amino-terminated polysiloxane is 2000-4000. The molar ratio of the modified amino-terminated polysiloxane to the alicyclic diamine is 1:4 to 1:9.
[0013] In some embodiments, the nanoscale hydrophilic fumed silica has a particle size of 10 nm to 30 nm and a specific surface area of 150 m². 2 / g~250m 2 / g; The particle size of the nano-zirconia is 20nm to 30nm; The silane coupling agent is either KH-550 or KH792; The additive is a hindered amine light stabilizer and / or an ultraviolet absorber, wherein the hindered amine light stabilizer is any one of 2,2,6,6-tetramethylpiperidine derivatives and 1,2,2,6,6-pentamethylpiperidine derivatives, and the ultraviolet absorber is any one of benzophenones and benzotriazoles. The organic solvent includes any one of aldimine and oxazolidine.
[0014] This invention also provides a method for preparing a high-transparency, non-destructive modified polyurea composite coating, comprising the following steps: Hexamethylene diisocyanate, isophorone diisocyanate, polycarbonate diol, and organic bismuth are polymerized to obtain component A, which is an aliphatic polyisocyanate prepolymer. Preparation of polysiloxane block-modified polyaspartic acid ester resin; Weigh out nano-sized hydrophilic fumed silica, nano-zirconia, silane coupling agent, additives and the polysiloxane block modified polyaspartic acid ester resin according to the weight ratio, mix and stir to obtain component B; At room temperature, components A and B are mixed in a weight ratio of 1:1 to 1:1.5, and organic solvent is added according to the weight ratio. The mixture is stirred at a speed of 100 rpm to 300 rpm for 2 min to 4 min, and then defoamed under vacuum to obtain the high-transparency non-destructive modified polyurea composite coating.
[0015] In some embodiments, the vacuum degree of the vacuum degassing is ≤0.1 Bar, and the degassing time is 5 min to 10 min.
[0016] Accordingly, the present invention provides an application of a high-transparency, non-destructive modified polyurea composite coating in the protective coating of painted ceramics.
[0017] Compared with the prior art, the present invention has the following beneficial effects: This invention provides a high-transparency, non-destructive modified polyurea composite coating, its preparation method, and its application. The high-transparency, non-destructive modified polyurea composite coating includes component A, component B, and an organic solvent. Component A utilizes the -OH group of polycarbonate diol to react with the -NCO groups of hexamethylene diisocyanate and isophorone diisocyanate to generate an aliphatic polyisocyanate prepolymer with urethane bonds. Due to the introduction of urethane bonds, the toughness of the composite coating and its adhesion to painted ceramics can be improved.
[0018] Component B of this invention is a composite resin body, prepared by stirring polysiloxane block-modified polyaspartic acid ester resin, nano-sized hydrophilic fumed silica, nano-zirconia, silane coupling agent, and additives. The nano-zirconia, as a multifunctional nanofiller, significantly enhances the wear resistance of the composite coating through high hardness and nano-size effect. Simultaneously, its high refractive index and dense filling characteristics maintain the high transparency and gloss of the composite coating, synergistically improving its hardness and hydrophobicity, thereby achieving high transparency and high physical protection. The polysiloxane block-modified polyaspartic acid ester resin is obtained by Michael addition reaction of modified amino-terminated polysiloxane, alicyclic diamine, and dialkyl maleate. Introducing polysiloxane alkyl aspartic acid ester segments during the synthesis stage ensures a uniform composite coating, guarantees easy cleaning performance, avoids refraction, and improves hydrophobicity and flexibility.
[0019] This invention obtains a high-transparency, non-destructive modified polyurea composite coating by controlling the weight ratio of component A to component B at 1:1 to 1:1.5, adding a small amount of organic solvent, and then defoaming under vacuum. It should be noted that the organic solvent can control the reaction rate of component A and component B, promote coating leveling, and ensure its gloss. Furthermore, the amount of organic solvent used is small, far lower than the organic solvent content in conventional coatings (exceeding 10%), making it more economical and environmentally friendly.
[0020] Therefore, the high-transparency, non-destructive modified polyurea composite coating prepared by this invention has the characteristics of high toughness, wear resistance, water resistance, and easy cleaning. It does not dissolve, soften, bubble, or peel off the organic pigments on the bottom layer of painted ceramics. After curing, it can maintain high transparency and high clarity, and does not produce oblique shadows or optical distortions. It is suitable for protective coatings for painted ceramics and can be widely used in the field of cultural relic and art protection. Attached Figure Description
[0021] Figure 1 A cross-sectional structural diagram of a painted ceramic piece coated with a high-transparency, non-destructive modified polyurea composite coating as a protective layer; Figure 2 Comparison of painted ceramics before and after applying a high-transparency, non-destructive modified polyurea composite coating as a protective layer. Detailed Implementation
[0022] To make the objectives, technical solutions, and advantages of this invention clearer, the invention will be further described in detail below with reference to the accompanying drawings and specific embodiments.
[0023] This invention provides a high-transparency, non-destructive modified polyurea composite coating, comprising component A, component B, and an organic solvent; Component A is an aliphatic polyisocyanate prepolymer, which is mainly obtained by polymerization reaction of hexamethylene diisocyanate, isophorone diisocyanate, polycarbonate diol, and organic bismuth. Component B is a composite resin, comprising the following raw materials in parts by weight: 100 parts of polysiloxane block-modified polyaspartic acid ester resin; 1 to 4 parts of nano-sized hydrophilic fumed silica; 0.5 to 5 parts of nano-zirconia; 0.5 to 3 parts of silane coupling agent; Additives: 1 to 2 parts.
[0024] The polysiloxane block-modified polyaspartic acid ester resin is mainly obtained by Michael addition reaction of modified amino-terminated polysiloxane, alicyclic diamine, and dialkyl maleate. The amount of the organic solvent is 0.5 to 1 part, based on 100 parts by weight of the polysiloxane block-modified polyaspartic acid ester resin.
[0025] The high-transparency, non-destructive modified polyurea composite coating provided by this invention comprises component A and component B. Component A is an aliphatic polyisocyanate prepolymer, and component B is a composite resin comprising polysiloxane block-modified polyaspartic acid ester resin, nano-scale hydrophilic fumed silica, nano-zirconia, silane coupling agent, and additives. The high-transparency, non-destructive modified polyurea composite coating of this invention features high toughness, wear resistance, and waterproofing. It does not dissolve, soften, bubble, or peel off the organic pigments on the underlying layer of painted ceramics. After curing, it maintains high optical transparency and high fidelity, without producing skewing or optical distortion.
[0026] The high-transparency, non-destructive modified polyurea composite coating of this invention also includes an organic solvent. Preferably, the organic solvent includes any one of aldehydes and imides or oxazolidines. The amount of the organic solvent used is small, and compared with conventional coatings on the market that contain more than 10% organic solvent, the composite coating provided by this invention is more environmentally friendly. It should be noted that by adding a small amount of organic solvent after mixing components A and B, this invention can control the reaction rate of components A and B, promote coating leveling, and ensure its gloss.
[0027] In some embodiments, component A is an aliphatic polyisocyanate prepolymer, which is prepared by the following method: (1) Mix hexamethylene diisocyanate monomer and isophorone diisocyanate monomer in a molar ratio to obtain mixture A; (2) Polycarbonate diol is added to the mixture A to obtain mixture B; (3) Under constant temperature conditions of 70℃~90℃, an organic bismuth catalyst was added dropwise to the mixture B, and the reaction was carried out for 2h~4h to obtain mixture C; (4) Remove the unreacted free isocyanate monomers from the mixture C to obtain the aliphatic polyisocyanate prepolymer.
[0028] Commonly available aliphatic polyisocyanate prepolymers, such as hexamethylene diisocyanate (HDI), isophorone diisocyanate (IPDI), and dicyclohexylmethane diisocyanate (hydrogenated MDI), have a fixed refractive index and a large shrinkage rate. After curing, they tend to pull on the organic pigments on the bottom layer of painted ceramics, causing them to peel off. In addition, their flexibility often fails to meet the requirements of precision, smoothness, color purity, and long-term stability required for artworks.
[0029] Therefore, this invention introduces polycarbonate diol (PCDL) to polymerize with HDI and IPDI under the action of an organic bismuth catalyst to obtain an aliphatic polyisocyanate prepolymer. Since the carbonate groups in the PCDL main chain and the cyclohexane ring of IPDI can effectively resist volume shrinkage, the shrinkage rate is reduced. After curing, it is not easy to produce orange peel or cracks due to volume shrinkage, and it will not even cause the organic pigments on the bottom layer of the painted ceramic to peel off or deform due to excessive tension.
[0030] Preferably, the organic bismuth includes, but is not limited to, bismuth neodecanoate, bismuth isooctanoate, and bismuth laurate.
[0031] Furthermore, the aliphatic polyisocyanate prepolymer of this invention, obtained by polymerizing PCDL, HDI, and IPDI, can effectively wet the organic pigments on the underlying layer of painted ceramics, enhancing color saturation. Due to its aliphatic or alicyclic structure, the prepolymer itself has high transparency, and the coating formed after curing is not prone to aging and yellowing, maintaining the original high-fidelity color of the organic pigments for a long time. Moreover, the prepolymer can balance flexibility and rigidity, forming a dense and tough cross-linked network that can firmly anchor the organic pigments and provide wear-resistant and chemical-resistant protection for the painted layer on the surface of the painted ceramics, preventing the organic pigments from peeling or fading.
[0032] Specifically, HDI has a straight-chain aliphatic structure with no side groups and a flexible molecular chain. The two -NCOs have similar activities. In contrast, IPDI has a six-membered ring alicyclic structure with a more rigid structure. The activities of the two -NCOs are different. By adjusting the molar ratio of HDI monomers and IPDI monomers, the molecular chain structure of the aliphatic polyisocyanate prepolymer can be effectively controlled, thereby balancing the mechanical properties and reaction rate of the composite coating.
[0033] In some embodiments, the molar ratio of hexamethylene diisocyanate monomer to isophorone diisocyanate monomer is 1:1 to 3:1. Within the above range, HDI and IPDI can balance the flexibility and rigidity of the aliphatic polyisocyanate prepolymer and control the rate at which the aliphatic polyisocyanate prepolymer in component A reacts with -NH- in component B to form urea bonds.
[0034] Furthermore, this invention introduces polycarbonate diol, utilizing the -OH group of polycarbonate diol to pre-consume some of the -NCO groups in HDI and IPDI, thereby introducing urethane bonds (-NH-CO-) into the aliphatic polyisocyanate prepolymer. This effectively slows down the rate at which the -NCO group in component A reacts with the -NH- group in component B to form urea bonds, extending the workability of the high-transparency, non-destructive modified polyurea composite coating, reducing the system viscosity, and making its application more flexible and convenient. In addition, the urethane bonds and the subsequently formed urea bonds can jointly construct a strong hydrogen bond network, improving the toughness of the high-transparency, non-destructive modified polyurea composite coating and its adhesion to painted ceramics.
[0035] In some embodiments, the number average molecular weight of the polycarbonate diol is 1000-2000, and the molar ratio of -NCO to -OH in the system is controlled to be 4:1-6:1. Within the above range, the proportion of urethane bonds in the aliphatic polyisocyanate prepolymer of component A can be precisely controlled, thereby precisely controlling the proportion of urea bonds to urethane bonds in the subsequent process. This effectively improves the long-term hydrolysis resistance and service life of the coating in a humid and hot environment, achieving high toughness, wear resistance, and waterproof performance.
[0036] Preferably, in this invention, under constant temperature conditions of 70℃ to 90℃, an organic bismuth catalyst is added dropwise to polymerize PCDL, HDI, and IPDI for 2 to 4 hours until the mass fraction of -NCO in the system is 10% to 15%. Unreacted isocyanate free monomers are then removed using a thin-film evaporator to obtain an aliphatic polyisocyanate prepolymer. The chemical reaction equation is shown below:
[0037] In some embodiments, the amount of organic bismuth added is 0.02wt% to 0.05wt% of the total mass of PCDL, HDI, and IPDI. Within this range, under the action of the organic bismuth catalyst, PCDL reacts with the -NCO of HDI to form an urethane bond. At the same time, the -NCO of IPDI attached to the cyclohexane ring has higher activity and will preferentially react with the -OH of PCDL to form an urethane bond. The -NCO with lower activity on the side chain of IPDI will remain on the aliphatic polyisocyanate prepolymer molecular chain and be used to form a urea bond with the -NH in component B later.
[0038] The present invention obtains the aliphatic polyisocyanate prepolymer of component A through the above-mentioned polymerization reaction method, which is beneficial to the formation of a microphase structure with clearly separated soft and hard segments in the high-transparency non-destructive polyurea composite coating, thereby improving its flexibility and wear resistance. In addition, the urea bonds formed by components A and B can endow the composite coating with excellent thermal stability and hydrolysis resistance. At the same time, the reaction process has good controllability and can effectively suppress branching side reactions and gelation.
[0039] Painted ceramic artworks are not only for collection but also used in public places such as squares and parks. This requires the surface coating of painted ceramic artworks to have certain easy-to-clean properties. However, in conventional coatings for non-fired ceramics, this problem is usually solved by adding silicone oil-based anti-graffiti additives. Although this method achieves easy cleaning, because these additives are added directly at room temperature after drying, they usually float on the surface of the coating, causing refraction and altering the artistic effect.
[0040] Therefore, component B of the present invention uses polysiloxane block-modified polyaspartic acid ester resin, and the modified polysiloxane is directly introduced during the synthesis stage, so that the cured coating has good uniformity and consistency, which can not only ensure easy cleaning performance, but also effectively avoid the occurrence of refraction.
[0041] In some embodiments, the polysiloxane block-modified polyaspartic acid ester resin is prepared by the following method: (1) The modified amino-terminated polysiloxane and alicyclic diamine were mixed in a molar ratio to obtain mixture D; (2) Under nitrogen protection, the mixture D is added dropwise to dialkyl maleate to obtain mixture E, wherein the molar ratio of -NH2 to -C=C- in mixture E is 1:1 to 1:1.05; (3) The mixture E is subjected to a Michael addition reaction at 40℃ to 60℃ for 12h to 24h to obtain mixture F; (4) The unreacted monomers in the mixture F are removed by vacuum to obtain the polysiloxane block-modified polyaspartic acid resin.
[0042] Specifically, the modified amino-terminated polysiloxane used in this invention provides flexible siloxane segments, while the alicyclic diamine provides a rigid alicyclic structure. By using the modified amino-terminated polysiloxane and the alicyclic diamine as amine components and controlling the molar ratio of the modified amino-terminated polysiloxane to the alicyclic diamine, the ratio of soft and hard segments in the polysiloxane block-modified polyaspartic acid ester resin (Si-PAE) can be precisely controlled, thereby achieving good flexibility and wear resistance in the composite coating. Furthermore, the modified amino-terminated polysiloxane provides low surface energy, making it difficult for contaminants such as dust, oil, and ink to adhere, thus giving the composite coating good hydrophobicity and maintaining good cleaning ability.
[0043] In some embodiments, the modified amino-terminated polysiloxane includes any one of amino-terminated diphenylsiloxane, polyether side-chain modified amino-terminated siloxane, amino-terminated poly(methylcyclohexyl)siloxane, and amino-terminated poly(methylcyclopentyl)siloxane. The alicyclic diamine includes any one of 4,4'-diaminodicyclohexylmethane and 3,3'-dimethyl-4,4'-diaminodicyclohexylmethane; The dialkyl maleate includes either diethyl maleate or dipropyl maleate.
[0044] Preferably, terminal aminodiphenylsiloxane can utilize the high molar refractive index of phenyl groups to regulate the coating refractive index to match the ceramic substrate, eliminating the oblique shadow effect caused by interfacial optical differences, thereby achieving high transparency; polyether side-chain modified terminal aminosiloxane utilizes polyether segments to effectively improve the anti-fogging performance of the coating surface and inhibit water mist condensation; terminal aminopoly(methylcyclohexyl)siloxane and terminal aminopoly(methylcyclopentyl)siloxane utilize the rigid structure of cycloalkyl side groups to improve the coating's resistance to thermo-oxidative aging while maintaining high transparency, giving the coating good anti-yellowing properties.
[0045] In some embodiments, the number average molecular weight of the modified amino-terminated polysiloxane is 2000-4000, and the molar ratio of the modified amino-terminated polysiloxane to the alicyclic diamine is 1:4-1:9. Within the above range, the modified amino-terminated polysiloxane and the highly active alicyclic diamine work synergistically to form a three-dimensional network structure, firmly anchoring the organic pigment particles in the bottom layer of the painted ceramic and effectively preventing the organic pigments from falling off.
[0046] Preferably, in this invention, a mixture of terminal aminodiphenylsiloxane and 4,4'-diaminodicyclohexylmethane is slowly added dropwise to a sufficient amount of diethyl maleate, with the molar ratio of -NH2 to -C=C- in the system controlled at 1:1 to 1:1.05. The mixture undergoes a Michael addition reaction at 40°C to 60°C for 12 to 24 hours. After the reaction, unreacted light components are removed under vacuum to obtain Si-PAE. The chemical reaction equation is shown below:
[0047] It should be noted that the Si-PAE described in this invention is prepared by a Michael addition reaction of modified amino-terminated polysiloxane, alicyclic diamine and dialkyl maleate. The alicyclic diamine and dialkyl maleate undergo a Michael addition reaction to generate polyaspartic acid ester segments, and the modified amino-terminated polysiloxane and dialkyl maleate undergo a Michael addition reaction to generate polysiloxane alkyl aspartic acid ester segments. The two segments are chemically bonded together to form a block copolymer structure.
[0048] This invention enhances the hydrophobicity and flexibility of composite coatings through polysiloxane alkyl aspartic ester segments. At the same time, the polysiloxane ester segments ensure that the composite coating has sufficient wear resistance and adhesion. The Si-PAE prepared by the above-mentioned Michael addition reaction can simultaneously exert the properties of polyaspartic ester and polysiloxane without increasing costs.
[0049] In some embodiments, in component B of the present invention, the nanoscale hydrophilic fumed silica has a particle size of 10 nm to 30 nm and a specific surface area of 150 m². 2 / g~250m 2 / g; The particle size of the nano-zirconia is 20nm to 30nm; The silane coupling agent is either KH-550 or KH792; The additive is a hindered amine light stabilizer and / or an ultraviolet absorber, wherein the hindered amine light stabilizer is any one of 2,2,6,6-tetramethylpiperidine derivatives and 1,2,2,6,6-pentamethylpiperidine derivatives, and the ultraviolet absorber is any one of benzophenones and benzotriazoles.
[0050] Preferably, the present invention uses nanoscale hydrophilic fumed silica as a rheology modifier, which is prepared by high-temperature hydrolysis of silicon tetrachloride in an oxyhydrogen flame and has a surface rich in silanol groups (Si-OH). Because the specific surface area of nanoscale hydrophilic fumed silica is as high as 150 m² / g, the present invention is particularly effective in this application. 2 / g~250m 2 / g, which makes it easy to form a three-dimensional network structure in composite coatings through hydrogen bonding. This three-dimensional network structure can effectively prevent the sedimentation of resin and filler, thereby improving the thixotropic and anti-sagging properties of composite coatings while improving the construction performance.
[0051] Preferably, the nano-zirconia can be a nano-zirconia dispersion, and the solvent of the nano-zirconia dispersion can be ethanol, n-butanol, isopropanol, xylene, acetone, etc., and the concentration of the nano-zirconia dispersion is 40% to 60%, but not limited thereto.
[0052] It should be noted that nano-zirconia, as a multifunctional nanofiller in composite coatings, significantly enhances the wear resistance of the composite coating through high hardness and nano-size effect. At the same time, by utilizing its high refractive index and dense filling characteristics, its weight part can be controlled between 0.5 and 5 parts to maintain the high transparency and gloss of the composite coating, and synergistically improve the hardness and hydrophobicity of the composite coating, thereby achieving high transparency and high physical protection.
[0053] Preferably, the silane coupling agent used in this invention can enhance the adhesion of the composite coating to painted ceramics and achieve good hydrophobicity and oleophobicity. The silane coupling agent used is KH-550 or KH792, but is not limited to these.
[0054] Preferably, the present invention employs hindered amine light stabilizers and / or ultraviolet absorbers, which helps to delay the photoaging process of composite coatings and painted organic pigments, thereby achieving a protective effect on painted ceramics.
[0055] This invention also provides a method for preparing a high-transparency, non-destructive modified polyurea composite coating, comprising the following steps: Hexamethylene diisocyanate, isophorone diisocyanate, polycarbonate diol, and organic bismuth are polymerized to obtain component A, which is an aliphatic polyisocyanate prepolymer. Preparation of polysiloxane block-modified polyaspartic acid ester resin; Weigh out nano-sized hydrophilic fumed silica, nano-zirconia, silane coupling agent, additives and the polysiloxane block modified polyaspartic acid ester resin according to the weight ratio, mix and stir to obtain component B; At room temperature, components A and B are mixed in a weight ratio of 1:1 to 1:1.5, and organic solvent is added according to the weight ratio. The mixture is stirred at a speed of 100 rpm to 300 rpm for 2 min to 4 min, and then defoamed under vacuum to obtain the high-transparency non-destructive modified polyurea composite coating.
[0056] Specifically, the present invention involves adding polycarbonate diol and, under the action of an organic bismuth catalyst, reacting it with hexamethylene diisocyanate and isophorone diisocyanate to prepare an aliphatic polyisocyanate prepolymer, thus obtaining component A.
[0057] Furthermore, in this invention, modified amino-terminated polysiloxane and alicyclic diamine are added to a sufficient amount of dialkyl maleate to carry out a Michael addition reaction to obtain polysiloxane block-modified polyaspartic acid ester resin.
[0058] Furthermore, in this invention, nano-sized hydrophilic fumed silica, nano-zirconia, silane coupling agent, additives, and the polysiloxane block-modified polyaspartic acid ester resin are weighed according to the weight ratio, and mixed and stirred evenly in a high-speed disperser to obtain component B, wherein component B is a composite resin body.
[0059] Preferably, the stirring speed is 1000 rpm to 2500 rpm and the stirring time is 20 min to 40 min. Within the above range, the polysiloxane block-modified polyaspartic acid ester resin can be uniformly dispersed with other fillers and additives.
[0060] Furthermore, this invention controls the weight ratio of component A to component B to be 1:1 to 1:1.5, then adds an organic solvent according to the weight ratio, and obtains a high-transparency, non-destructive modified polyurea composite coating after vacuum defoaming. The amount of organic solvent used is small, which ensures environmental protection while controlling the reaction rate of component A and component B, promoting coating leveling, and ensuring its gloss.
[0061] Furthermore, if the weight ratio of component A to component B is less than 1:1, the excess -NCO in component A will react with moisture in the air to generate carbon dioxide, leading to foaming and decreased mechanical properties of the composite coating; if the weight ratio of component A to component B is greater than 1:1.5, the composite coating may experience problems such as surface stickiness and low strength.
[0062] It should be noted that the -NCO in component A reacts with the -NH- in component B to form urea bonds. Within the above weight ratio range, the reaction rate of components A and B can be effectively controlled, extending the workability of the composite coating to 80 min to 120 min.
[0063] In some embodiments, by controlling the vacuum degree of vacuum degassing to ≤0.1 Bar and the degassing time to 5 min to 10 min, a high-transparency, non-destructive modified polyurea composite coating with almost no bubbles can be obtained, laying the foundation for obtaining a bubble-free high-transparency, non-destructive modified polyurea composite coating protective layer after subsequent coating and curing.
[0064] This invention allows for coating painted ceramics using either a fine brush or low-pressure, high-atomization spraying. When using a fine brush, a sheep's hair brush or a high-density soft brush is used to apply the composite coating gently in the direction of the brushstrokes. When using low-pressure, high-atomization spraying, the working air pressure of the spray gun is <0.15MPa, and the spraying distance is maintained at 15cm–20cm to ensure the composite coating is evenly applied to the surface of the painted ceramic. After coating, the painted ceramic is placed in a dust-free, well-ventilated environment and allowed to cure naturally at room temperature for 12–24 hours, resulting in a high-transparency, non-destructive modified polyurea composite coating protective layer on the surface of the painted ceramic.
[0065] like Figure 1 As shown, the painted ceramic includes a ceramic substrate 1 and a painted layer 2. A high-transparency, non-destructive modified polyurea composite coating protective layer 3 is applied to the surface of the painted ceramic, providing protection for both the ceramic substrate 1 and the painted layer 2. Figure 2As shown, the painted patterns before being coated with the high-transparency, non-destructive modified polyurea composite coating protective layer had low color saturation and were prone to fading when wiped, causing significant inconvenience for cleaning. However, after being coated with the high-transparency, non-destructive modified polyurea composite coating protective layer, the painted patterns had significantly improved color saturation, bright colors, and were easy to clean. At the same time, the organic pigments on the bottom layer of the painted ceramic did not spread or bleed. The protective layer formed after the composite coating cured was mirror-smooth, maintaining high transparency and high clarity, without producing slant shadows or optical distortion. This indicates that the high-transparency, non-destructive modified polyurea composite coating does not damage the organic pigments on the bottom layer of the painted ceramic, and can achieve high color fidelity while maintaining high optical transparency.
[0066] Accordingly, the present invention provides an application of a high-transparency, non-destructive modified polyurea composite coating in the protective coating of painted ceramics.
[0067] Therefore, the high-transparency, non-destructive modified polyurea composite coating prepared by the above method has the characteristics of high toughness, wear resistance, water resistance, and easy cleaning. It does not dissolve, soften, bubble, or peel off the organic pigments on the bottom layer of painted ceramics. After curing, it can maintain high transparency and high clarity, and does not produce slant shadows or optical distortions. It is suitable for use in protective coatings for painted ceramics.
[0068] The following detailed description, with reference to specific embodiments, will further illustrate this point.
[0069] 1. Preparation Example 1 Example 1 of this invention provides a high-transparency, non-destructive modified polyurea composite coating, its preparation method, and its application. The high-transparency, non-destructive modified polyurea composite coating comprises component A, component B, and an organic solvent. The preparation method of the high-transparency, non-destructive modified polyurea composite coating includes the following steps: (1) Preparation of aliphatic polyisocyanate prepolymer (component A) Component A in Example 1 of this invention is an aliphatic polyisocyanate prepolymer, obtained by polymerization of hexamethylene diisocyanate, isophorone diisocyanate, polycarbonate diol, and organic bismuth. The specific steps are as follows: Hexamethylene diisocyanate (HDI) monomer and isophorone diisocyanate (IPDI) monomer were mixed at a molar ratio of 2:1 and added to a reactor. Then, polycarbonate diol (PCDL) with a number average molecular weight of 1000 was added. The molar ratio of -NCO to -OH was controlled at 5:1. Under constant temperature of 80°C and nitrogen protection, 0.05 wt% organic bismuth catalyst was added dropwise. After reacting for 3 hours, the mass fraction of -NCO in the system was measured to be 12%. The free monomers were then removed by a thin-film evaporator to obtain aliphatic polyisocyanate prepolymer (component A).
[0070] (2) Preparation of polysiloxane block-modified polyaspartic acid ester (Si-PAE) resin The polysiloxane block-modified polyaspartic acid ester (Si-PAE) resin described in Example 1 of this invention is obtained by a Michael addition reaction of modified amino-terminated polysiloxane, alicyclic diamine, and dialkyl maleate. The specific steps are as follows: A terminal aminodiphenylsiloxane with a molecular weight of 2000 was mixed with 4,4'-diaminodicyclohexylmethane (PACM) at a molar ratio of 1:5. Under nitrogen protection, the mixture was added dropwise to diethyl maleate (DEM). The molar ratio of -NH2 to -C=C- was controlled at 1:1.05. The Michael addition reaction was carried out in a reactor at a constant temperature of 50°C for 18 hours. After the reaction was completed, the unreacted light components were removed under vacuum at 100°C to obtain polysiloxane block-modified polyaspartic acid ester (Si-PAE) resin.
[0071] (3) Preparation of composite resin (component B) Component B in Example 1 of this invention is a composite resin body, which is prepared by mixing and stirring the following raw materials in parts by weight, and the specific steps are as follows: Weigh out 100 parts of the above-mentioned polysiloxane block modified polyaspartic acid ester (Si-PAE) resin, 2.5 parts of nano-grade hydrophilic fumed silica, 2 parts of nano-zirconia dispersion, 1.5 parts of silane coupling agent (KH-550), and 1 part of hindered amine light stabilizer, and mix them evenly in a high-speed disperser to obtain the composite resin body (component B).
[0072] (4) Preparation and application of high-transparency non-destructive modified polyurea composite coatings In Example 1 of this invention, the above-mentioned components A and B were mixed evenly at a weight ratio of 1:1.2, and then 0.6 parts of aldehyde imine were added. The mixture was stirred at 300 rpm for 3 minutes, and then placed in a vacuum chamber and vacuumed at a vacuum degree of 0.1 Bar for 5 minutes to remove bubbles, thereby obtaining a high-transparency, non-destructive modified polyurea composite coating. The composite coating was applied with a fine brush along the direction of the painting strokes, and left at room temperature for 24 hours to allow it to fully cure, thereby obtaining a high-transparency, non-destructive modified polyurea composite coating protective layer coated on the surface of the painted ceramic.
[0073] Example 2 Example 2 of this invention provides a high-transparency, non-destructive modified polyurea composite coating, its preparation method, and its application. The high-transparency, non-destructive modified polyurea composite coating comprises component A, component B, and an organic solvent. The preparation method of the high-transparency, non-destructive modified polyurea composite coating includes the following steps: (1) Preparation of aliphatic polyisocyanate prepolymer (component A) The preparation of component A in Example 2 of this invention is basically the same as that in Example 1, except that: The molar ratio of hexamethylene diisocyanate (HDI) monomer to isophorone diisocyanate (IPDI) monomer is 1:1; The polycarbonate diol (PCDL) has a molecular weight of 2000.
[0074] (2) Preparation of polysiloxane block-modified polyaspartic acid ester (Si-PAE) resin The preparation of the polysiloxane block-modified polyaspartic acid ester (Si-PAE) resin in Example 2 of this invention is basically the same as that in Example 1, except that: The molar ratio of the terminal aminodiphenylsiloxane to 4,4'-diaminodicyclohexylmethane (PACM) is 1:4.
[0075] (3) Preparation of composite resin (component B) Component B in Embodiment 2 of the present invention is a composite resin body, which is prepared by mixing and stirring the following raw materials in parts by weight, and the specific steps are as follows: Weigh out 100 parts of the above-mentioned polysiloxane block modified polyaspartic acid ester (Si-PAE) resin, 1.5 parts of nano-grade hydrophilic fumed silica, 3 parts of nano-zirconia dispersion, 1 part of silane coupling agent, and 1.5 parts of ultraviolet absorber, and mix them evenly in a high-speed disperser to obtain the composite resin body (component B).
[0076] (4) Preparation and application of high-transparency non-destructive modified polyurea composite coatings In Example 2 of this invention, component A and component B were mixed evenly at a weight ratio of 1:1, and then 0.5 parts of oxazolidine were added. The mixture was stirred at 300 rpm for 3 minutes, and then placed in a vacuum chamber and vacuumed at a vacuum degree of 0.1 Bar for 5 minutes to remove bubbles, thereby obtaining a high-transparency, non-destructive modified polyurea composite coating. Subsequently, it was uniformly sprayed onto the surface of the painted ceramic using an HVLP low-pressure spray gun (working air pressure of 0.12 MPa), and cured at room temperature for 24 hours to obtain a high-transparency, non-destructive modified polyurea composite coating protective layer on the surface of the painted ceramic.
[0077] Example 3 Example 3 of this invention provides a high-transparency, non-destructive modified polyurea composite coating, its preparation method, and its application. The high-transparency, non-destructive modified polyurea composite coating comprises component A, component B, and an organic solvent. The preparation method of the high-transparency, non-destructive modified polyurea composite coating includes the following steps: (1) Preparation of aliphatic polyisocyanate prepolymer (component A) The preparation of component A in Example 3 of this invention is basically the same as that in Example 1, except that: The molar ratio of hexamethylene diisocyanate (HDI) monomer to isophorone diisocyanate (IPDI) monomer is 3:1.
[0078] (2) Preparation of polysiloxane block-modified polyaspartic acid ester (Si-PAE) resin The preparation of the polysiloxane block-modified polyaspartic acid ester (Si-PAE) resin in Example 3 of this invention is basically the same as that in Example 1, except that: The molar ratio of the terminal aminodiphenylsiloxane to 4,4'-diaminodicyclohexylmethane (PACM) is 1:8.
[0079] (3) Preparation of composite resin (component B) Component B in Embodiment 3 of the present invention is a composite resin body, which is prepared by mixing and stirring the following raw materials in parts by weight, and the specific steps are as follows: Weigh out 100 parts of the above-mentioned polysiloxane block-modified polyaspartic acid ester (Si-PAE) resin, 4 parts of nano-sized hydrophilic fumed silica, 1.5 parts of nano-zirconia dispersion, 2 parts of silane coupling agent, and 1 part of light stabilizer, and mix them evenly in a high-speed disperser to obtain the composite resin body (component B).
[0080] (4) Preparation and application of high-transparency non-destructive modified polyurea composite coatings In Example 3 of this invention, component A and component B were mixed evenly at a weight ratio of 1:1.5, and then 1 part of oxazolidine was added. The mixture was stirred at 300 rpm for 3 minutes, and then placed in a vacuum chamber and vacuumed at a vacuum degree of 0.1 Bar for 5 minutes to remove bubbles, thereby obtaining a high-transparency, non-destructive modified polyurea composite coating. The composite coating was applied gently to specific areas using a high-density soft brush and cured at room temperature for 24 hours to obtain a high-transparency, non-destructive modified polyurea composite coating protective layer coated on the surface of painted ceramics.
[0081] Comparative Example 1 Comparative Example 1 of this invention provides a conventional commercially available composite coating, its preparation method, and its application. The conventional commercially available composite coating includes component A and component B. The preparation method of the conventional commercially available composite coating includes the following steps: (1) Component A: Commercially available HDI trimer (Bayer N3300) is used.
[0082] (2) Component B: Commercially available ordinary polyaspartic acid ester resin (aspartic polyurea F420) is used. This polyaspartic acid ester resin does not contain polysiloxane blocks. To ensure leveling, 20% xylene by mass is added as a solvent.
[0083] (3) Coating application: Mix component A and component B at a weight ratio of 1:1 evenly, apply the mixture to the same painted ceramic surface as in Example 1 using a regular spray gun, and cure at room temperature for 24 hours to obtain a traditional commercially available composite coating protective layer coated on the painted ceramic surface.
[0084] 2. Testing The performance of the cured painted ceramic samples of Examples 1-3 and Comparative Example 1 was tested.
[0085] (1) Test method Coating transmittance (500nm): The composite coatings prepared in Examples 1-3 and Comparative Example 1 were coated onto glass slides to form coatings. Uncoated glass slides were used as blank controls. The transmittance of the coatings in Examples 1-3 and Comparative Example 1 was tested using a UV-Vis spectrophotometer with an integrating sphere accessory and a wavelength of 500nm.
[0086] Coating adhesion: The cross-cut test was used. A grid was drawn on the coating surface of Examples 1-3 and Comparative Example 1 with a knife. The coating was then peeled off with tape, and the coating adhesion was judged based on the area of coating peeling off.
[0087] Surface water droplet angle: Using a contact angle meter, 2 μL to 10 μL of deionized water were dropped onto the coating surface of Examples 1 to 3 and Comparative Example 1 respectively using a micro-syringe. After the droplets stabilized, the surface water droplet contact angle was calculated.
[0088] (2) The test results are shown in Table 1: Table 1 shows the test results of Examples 1-3 and Comparative Example 1.
[0089] As shown in Table 1, the traditional commercially available composite coating provided in Comparative Example 1 has a short working time. After being applied to the surface of painted ceramics and cured at room temperature, the organic pigments in the bottom layer of the painted ceramics showed obvious dissolution and smudging. The coating was generally smooth but had oblique shadows and slight bubbles. The coating had low light transmittance, poor adhesion, and poor surface hydrophobicity.
[0090] In contrast, the high-transmittance, non-destructive modified polyurea composite coatings provided in Examples 1-3 of this invention have a long working time. After being coated on the surface of painted ceramics and cured at room temperature, the organic pigments in the bottom layer of the painted ceramics do not dissolve or bleed. The composite coating has a mirror-like smooth surface without shadows or bubbles, a light transmittance of >95%, strong adhesion, and a surface water droplet angle ≥100°.
[0091] Furthermore, Example 2 exhibits the largest surface water droplet angle and the best hydrophobicity, further demonstrating that by increasing the molar ratio of terminal aminodiphenylsiloxane to PACM, increasing the polysiloxane blocks in the composite coating, and increasing the weight proportion of nano-zirconia dispersion, the waterproof performance of the composite coating can be improved.
[0092] Therefore, the high-transparency, non-destructive modified polyurea composite coating provided by this invention has the characteristics of high toughness, wear resistance, water resistance, and easy cleaning. It does not dissolve, soften, bubble, or peel off the organic pigments on the bottom layer of painted ceramics. After curing, it can maintain high transparency and high clarity, and does not produce slant shadows or optical distortions. It is suitable for use in protective coatings for painted ceramics.
[0093] The above description is merely a preferred embodiment of the present invention and should not be construed as limiting the scope of the invention. Therefore, any equivalent variations made in accordance with the claims of the present invention are still within the scope of the present invention.
Claims
1. A high-transparency, non-destructive modified polyurea composite coating, characterized in that, Includes component A, component B, and organic solvent; Component A is an aliphatic polyisocyanate prepolymer, which is mainly obtained by polymerization reaction of hexamethylene diisocyanate, isophorone diisocyanate, polycarbonate diol, and organic bismuth. Component B is a composite resin, comprising the following raw materials in parts by weight: 100 parts of polysiloxane block-modified polyaspartic acid ester resin; 1 to 4 parts of nano-sized hydrophilic fumed silica; 0.5 to 5 parts of nano-zirconia; 0.5 to 3 parts of silane coupling agent; 1 to 2 parts of auxiliary agent; The polysiloxane block-modified polyaspartic acid ester resin is mainly obtained by Michael addition reaction of modified amino-terminated polysiloxane, alicyclic diamine, and dialkyl maleate. The amount of the organic solvent is 0.5 to 1 part, based on 100 parts by weight of the polysiloxane block-modified polyaspartic acid ester resin.
2. The high-transparency, non-destructive modified polyurea composite coating according to claim 1, characterized in that, The aliphatic polyisocyanate prepolymer is prepared by the following method: (1) Mix hexamethylene diisocyanate monomer and isophorone diisocyanate monomer in a molar ratio to obtain mixture A; (2) Polycarbonate diol is added to the mixture A to obtain mixture B; (3) Under constant temperature conditions of 70℃~90℃, an organic bismuth catalyst was added dropwise to the mixture B, and the reaction was carried out for 2h~4h to obtain mixture C; (4) Remove the unreacted free isocyanate monomers from the mixture C to obtain the aliphatic polyisocyanate prepolymer.
3. The high-transparency, non-destructive modified polyurea composite coating according to claim 1 or 2, characterized in that, The molar ratio of the hexamethylene diisocyanate monomer to the isophorone diisocyanate monomer is 1:1 to 3:1; The number-average molecular weight of the polycarbonate diol is 1000-2000; The amount of organic bismuth added is 0.02wt% to 0.05wt%.
4. The high-transparency, non-destructive modified polyurea composite coating according to claim 2, characterized in that, The molar ratio of -NCO to -OH in mixture B is 4:1 to 6:1; The mass fraction of -NCO in the mixture C is 10% to 15%.
5. The high-transparency, non-destructive modified polyurea composite coating according to claim 1, characterized in that, The polysiloxane block-modified polyaspartic acid ester resin is prepared by the following method: (1) The modified amino-terminated polysiloxane and alicyclic diamine were mixed in a molar ratio to obtain mixture D; (2) Under nitrogen protection, the mixture D is added dropwise to dialkyl maleate to obtain mixture E, wherein the molar ratio of -NH2 to -C=C- in mixture E is 1:1 to 1:1.05; (3) The mixture E is subjected to a Michael addition reaction at 40℃ to 60℃ for 12h to 24h to obtain mixture F; (4) The unreacted monomers in the mixture F are removed by vacuum to obtain the polysiloxane block-modified polyaspartic acid resin.
6. The high-transparency, non-destructive modified polyurea composite coating according to claim 1, characterized in that, The modified amino-terminated polysiloxane includes any one of amino-terminated diphenylsiloxane, polyether side-chain modified amino-terminated siloxane, amino-terminated poly(methylcyclohexyl)siloxane, and amino-terminated poly(methylcyclopentyl)siloxane. The alicyclic diamine includes any one of 4,4'-diaminodicyclohexylmethane and 3,3'-dimethyl-4,4'-diaminodicyclohexylmethane; The dialkyl maleate includes either diethyl maleate or dipropyl maleate. The number-average molecular weight of the modified amino-terminated polysiloxane is 2000-4000. The molar ratio of the modified amino-terminated polysiloxane to the alicyclic diamine is 1:4 to 1:
9.
7. The high-transparency, non-destructive modified polyurea composite coating according to claim 1, characterized in that, The nanoscale hydrophilic fumed silica has a particle size of 10 nm to 30 nm and a specific surface area of 150 m². 2 / g~250m 2 / g; The particle size of the nano-zirconia is 20nm to 30nm; The silane coupling agent is either KH-550 or KH792; The additive is a hindered amine light stabilizer and / or an ultraviolet absorber, wherein the hindered amine light stabilizer is any one of 2,2,6,6-tetramethylpiperidine derivatives and 1,2,2,6,6-pentamethylpiperidine derivatives, and the ultraviolet absorber is any one of benzophenones and benzotriazoles. The organic solvent includes any one of aldimine and oxazolidine.
8. A method for preparing a high-transparency, non-destructive modified polyurea composite coating as described in claims 1-7, characterized in that, Includes the following steps: Hexamethylene diisocyanate, isophorone diisocyanate, polycarbonate diol, and organic bismuth are polymerized to obtain component A, which is an aliphatic polyisocyanate prepolymer. Preparation of polysiloxane block-modified polyaspartic acid ester resin; Weigh out nano-sized hydrophilic fumed silica, nano-zirconia, silane coupling agent, additives and the polysiloxane block modified polyaspartic acid ester resin according to the weight ratio, mix and stir to obtain component B; At room temperature, components A and B are mixed in a weight ratio of 1:1 to 1:1.5, and organic solvent is added according to the weight ratio. The mixture is stirred at a speed of 100 rpm to 300 rpm for 2 min to 4 min, and then defoamed under vacuum to obtain a high-transparency, non-destructive modified polyurea composite coating.
9. The method for preparing the high-transparency, non-destructive modified polyurea composite coating according to claim 8, characterized in that, The vacuum degree of the vacuum degassing is ≤0.1 Bar, and the degassing time is 5 min to 10 min.
10. The application of a high-transparency, non-destructive modified polyurea composite coating as described in claims 1 to 7 in the protective coating of painted ceramics.